Correlations of High-pT Hadrons and Jets in ALICE - Filip Krizek (Universe, 2019)
There are two prominent experimental signatures of quark–gluon plasma creation in ultra-relativistic heavy-ion collisions: the jet quenching phenomenon and the azimuthal-momentum space-anisotropy of final-state particle emission. Recently, the latter signature was also observed in lighter collision systems such as p–Pb or pp. This raises a natural question of whether in these systems, the observed collectivity is also accompanied by jet quenching. In this paper, we overview ALICE measurements of the jet quenching phenomenon studied using semi-inclusive distributions of track-based jets recoiling from a high-transverse momentum ( <semantics> p T </semantics> ) hadron trigger in Pb–Pb and p–Pb collisions at LHC energies. The constructed coincidence observable, the per trigger normalized yield of associated recoil jets, is corrected for the complex uncorrelated jet background, including multi-partonic interactions, using a data-driven statistical subtraction method. In the p–Pb data, the observable was measured in events with different underlying event activity and was utilized to set an upper limit on the average medium-induced out-of-cone energy transport for jets with resolution parameter <semantics> R = 0.4 </semantics> . The associated jet momentum shift was found to be less than 0.4 GeV/c at 90% confidence.